2018
DOI: 10.1002/clc.23078
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and electrocardiographic subclinical myocardial injury: Results from National Health and Nutrition Examination Survey‐III

Abstract: Background Association of cardiovascular disease (CVD) with nontraditional risk factors such as vitamin D deficiency has been examined previously. An investigation of the association of vitamin D with subclinical myocardial injury (SC‐MI) based on an electrocardiographic score is a simple, cost‐effective and innovative way to explore this relationship. Hypothesis We hypothesize that low vitamin D levels will be associated with prevalent SC‐MI independent of traditional CVD risk factors, lifestyle factors, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
(47 reference statements)
3
9
0
Order By: Relevance
“…However, this study was conducted in mice, which might make it problematic to directly transfer these findings to the human organism. Overall, these results are consistent with epidemiological studies reporting serum 25(OH)D to be inversely correlated with CAD and myocardial injury [65,68]. However, the possibility of unknown confounding factors in these cross-sectional studies cannot be excluded.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, this study was conducted in mice, which might make it problematic to directly transfer these findings to the human organism. Overall, these results are consistent with epidemiological studies reporting serum 25(OH)D to be inversely correlated with CAD and myocardial injury [65,68]. However, the possibility of unknown confounding factors in these cross-sectional studies cannot be excluded.…”
Section: Discussionsupporting
confidence: 90%
“…The third group (reference) with serum-25(OH)D > 30 ng/mL had a prevalence of SC-MI = 19.5%. A comparison of groups one and three revealed that SC-MI was inversely associated with 25(OH)D levels with an odds ratio (OR) of 1.27 (95% CI: 1.04-1.55) after adjustments for potential confounders [65]. Hence, the study found a significant incremental increase in SC-MI prevalence associated with vitamin D deficiency (p = 0.04).…”
Section: Association Between Serum Vitamin D and Myocardial Injurymentioning
confidence: 75%
See 2 more Smart Citations
“…In line with other previous large studies that demonstrated a potential correlation between 25 (OH)D de ciency and subclinical myocardial injury and with sensitive neuropathy (22)(23)(24)(25), we hypothesized that vitamin D de ciency is correlated to SMI.…”
Section: Introductionsupporting
confidence: 68%